2009
DOI: 10.4049/jimmunol.0801375
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and FK506 Inhibit Expression of Distinct Subsets of Chemokines in Human Mast Cells

Abstract: Mast cells produce a large amount of several chemokines after cross-linking of FcεRI and participate in the pathogenesis of allergic diseases. The objective of this study was to comprehensively investigate FcεRI-mediated chemokine induction in human mast cells and the effect of a corticosteroid (dexamethasone) and a calcineurin inhibitor (FK506). Human peripheral blood-derived mast cells were stimulated with anti-IgE Ab in the presence of dexamethasone or FK506. Gene expression profiles were evaluated using Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 73 publications
(79 reference statements)
3
34
0
Order By: Relevance
“…Dermal mast cells are strong candidates, as they express TLR7 and produce cytokines upon Imi treatment (24). Recent studies have also shown that mast cells can produce CCL2 after anti-IgE stimulation (36). We observed that mast cells produced significant amounts of CCL2 after Imi treatment, therefore strengthening our hypothesis that mast cells are responsible for CCL2 production and subsequent pDC recruitment after topical Imi application.…”
Section: Discussionsupporting
confidence: 77%
“…Dermal mast cells are strong candidates, as they express TLR7 and produce cytokines upon Imi treatment (24). Recent studies have also shown that mast cells can produce CCL2 after anti-IgE stimulation (36). We observed that mast cells produced significant amounts of CCL2 after Imi treatment, therefore strengthening our hypothesis that mast cells are responsible for CCL2 production and subsequent pDC recruitment after topical Imi application.…”
Section: Discussionsupporting
confidence: 77%
“…Although they do not inhibit histamine release in human mast cells [107], they can reduce cytokine secretion by mast cells [108]. A recent study showed that topical corticosteroids (dexamethasone) treatment inhibited FcεRI-mediated up-regulation of chemokines, CCL2, CCL7, CXCL3, and CXCL8, in mast cells [109]. Calcineurin inhibitors, such as tacrolimus and pimecrolimus, have been approved by the FDA to treat moderate and severe AD [110].…”
Section: The Role Of Mast Cells Suggested By the Effect Of Therapeutimentioning
confidence: 97%
“…15,17 We obtained tarsal giant papilla tissues from refractory AKC/VKC patients, all of whom were treated with topical dexamethasone eye drops for at least 4 weeks (Table 1), so treatment may have downregulated the CCL2 expression as reported previously. 18 Nonetheless, significantly higher CCL2 mRNA expression in samples from giant papillae than in conjunctival tissues obtained from conjunctivochalasis patients was observed by real-time PCR analysis (Fig. 5).…”
Section: Ccl2 Expression and Degranulation In Mast Cellsmentioning
confidence: 99%